The Effect of Jigsaw towards Third Year Students' Learning Interest in IAIN Bukittinggi - Hasnawati Hasnawati (State Institute of Islamic Studies Imam Bonjol Padang, 2016)
This research aims to determine: 1). The implementation of Jigsaw in test and  evaluation course for third semester students of Islamic education department in IAIN Bukittinggi; 2). The types of students' learning interest in test and evaluation course; and 3). The effect of Jigsaw towards students' learning interest at Islamic education department in IAIN Bukittinggi. This research was conducted through survey method using regression analysis with one predictor. The total population in this research is 353 students in which 11.9% of them is taken as sample (42 students). The data were collected through questionnaire, documentation, and observation. The findings of the study showed that: 1). Jigsaw is in the "average" category with the mean score 66 in 65-67 interval; 2). Third semester students' learning interest of Islamic education department in IAIN Bukittinggi is in "average" category with the mean score of 65.95 in 65-67 interval; and 3). There is a positive effect of Jigsaw towards learning interest in test and evaluation course for third semester students of Islamic education department in IAIN Bukittinggi, which is demonstrated from the statistical analysis rxy= 0.6365 while from hypothesis testing by simple regression analysis, it is obtained that Y = 0.5182 X + 31.3701. it is concluded that there is significant effect of Jigsaw towards students' learning interest in test and evaluation course for third semester students of Islamic education major in IAIN Bukittinggi.